Pemanfaatan Limbah Ternak untuk Rumah Pangan Lestari dalam Upaya Penanganan Stunting di Desa Gelangsar Kabupaten Lombok Barat - Wanadiatri, Halia; Juniawan, Alvin; Fathurrahman, Fathurrahman; Wedowati, Endang Retno; Rejeki, Fungki Sri; Haryanta, Dwi (Jurnal Pengabdian UNDIKMA, 2024)
This community service activity aims to increase the understanding and skills of community members in utilizing livestock waste for sustainable food sources to handle stunting in Gelangsar Village, West Lombok Regency. The method of implementing this activity was through KOSABANGSA program outreach, training, and mentoring. The evaluation instrument for this activity used an environmental observation sheet and assesses the participation and activeness of participants during the activity. The results of this service activity showed that the community has the ability to process cowshed waste (solid) into 40 bags of compost, create a sustainable food house area using polybags in 8 groups spread throughout the village, and one KRPL point on land with an area of around 250 m2, and the types of plants were spinach, tomatoes, eggplant, chilies, mustard greens, lettuce, basil, long beans, family medicinal plants, and others. Guidance and assistance need to be continued considering that the community was very enthusiastic about being able to overcome stunting in Gelangsar village and at the same time wants to become an organic vegetable producer.